Influence Of The Monitoring And Control Strategies Of Indigenous And Expatriate Nigerian Contractors On Project Outcome - Idoro, Godwin Iroroakpo (Penerbit Universiti Sains Malaysia, 2012)
Monitoring and control are very important management functions for ensuring that project objectives are fully achieved. This study compares the level and effectiveness of the efforts of indigenous and expatriate Nigerian contractors on project monitoring and control. The aim of this study is to establish whether the project monitoring and control efforts of the contractors contribute to an improved project outcome. The study's objectives are to compare the frequencies at which project monitoring and control strategies are used by Nigerian contractors and their influence on project outcome. A field survey was conducted using a sample of 86 contractors selected by stratified random sampling. The data were collected using structured questionnaires and analysed using the mean, t-test and Spearman correlation test. The results of the study reveal that indigenous contractors carry out project control strategies more frequently than expatriate contractors. Furthermore, three of the eight monitoring and control strategies influence the project outcome, while the remaining strategies do not; this result indicates that while some of the strategies are effective, others are not. Contractors should thus ensure that their project monitoring and control efforts are directed towards improving the entire outcomes of their projects.